(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
Due to the fact that European markets are currently going through a financial crisisand the economy is significantly slowing down the Lisbon strategy for growth and employment is experiencing a new appreciation, as it is newly considered to be anessential instrument for the European Union to avoid the tendency towards long-lastingrecession. The present article examines, the results obtained by the Europe of the 27 in relation to the targets defined in Lisbon relative to the information society and the information and communication technologies (ICT) under the timeframe ofbeing one year before the fixed horizon of 2010.